(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, issues such as the socio-spiritual essence of a person in Sufism, his activities in real life, the issue of his relationship with society and people, and the ways of educating a perfect person on the path of Sufism of the Naqshbandi doctrine are philosophically analyzed.